Relasi Gender, Tekanan Ekonomi, Manajemen Keuangan, Strategi Nafkah, dan Kualitas Hidup pada Keluarga Nelayan - Berti Kumalasari; Tin Herawati; Megawati Simanjuntak (Jurnal Ilmu Keluarga dan Konsumen, 2018)
The high cost of living in various aspects becomes a challenge that must be faced by the family today, so that family must have a strategy in the management of resources to prevent the occurrence conflict and trigger economic pressure on the family, especially among fishermen families. This study aimed to determine the effect of gender relations, economic pressures, financial management and livelihood strategies on the quality of life of fishermen families. This research used quantitative study design. The research location was Mayangan Village, Legon Kulon Subdistrict, Subang Regency, West Java. The place of this study was selected based on the livelihood of the dominant fisherman population, is Mayangan Village. Respondents in this research were fisherman's wife and willing to be the respondent. The respondents were 60 fishermen's wives. Respondents were selected by using simple random sampling technique. Primary data were collected directly using interview techniques using structured questionnaires. The results showed that economic pressure and financial management influence significantly toward quality of life, financial management and gender relations influence significantly toward livelihood strategy. The implication of this research is the government should provide assistance to the wife in the form of tips in overcoming the economic pressure, so it is necessary to develop family empowerment program with issues in gender relation, financial management and livelihood strategy to solve family problems.